Doxycycline release and antibacterial activity from PMMA/PEO electrospun fiber mats (Journal of Applied Oral Science, 2022)
Objective: To investigate the use of polymethyl methacrylate (PMMA) electrospun fiber mats containing different amounts of polyethylene oxide (PEO) as a doxycycline delivery system and to test antibacterial activity against an oral pathogen. Methodology: PMMA powders or PEO (mol wt 200 Kd) (10,20,30% w/w/) were dissolved in N, N-dimethylformamide (DMF) to obtain a final polymer concentration of 15% in DMF (w/v). 2% Doxycycline monohydrate was added to the solutions and submitted to vortex mixing. The solution was transferred to a plastic syringe and fit into a nanofiber electrospinning unit. The parameters applied were: voltage at 17.2 kV; distance of 20 cm between the needle tip and the collector plate; target speed at 2 m/min; and transverse speed at 1cm/min. Syringe pump speed was 0.15 mm/min. The drug release analysis was performed by removing aliquots of the drug-containing solution (in PBS) at specific periods. Doxycycline release was quantified using RP-HPLC. Fiber mats from all groups had their antibacterial action tested against S. mutans based on inhibition halos formed around the specimens. The experiments were performed in triplicate. Gravimetric analysis at specific periods was performed to determine any polymer loss. Morphological characterization of the electrospun fibers was completed under an optical microscope followed by SEM analysis. Results: The addition of PEO to the PMMA fibers did not affect the appearance and diameter of fibers. However, increasing the %PEO caused higher doxycycline release in the first 24 h. Fibers containing 30% PEO showed statistically significant higher release when compared with the other groups. Doxycycline released from the fibers containing 20% or 30% of PEO showed effective against S. mutans. Conclusion: The incorporation of PEO at 20% and 30% into PMMA fiber mat resulted in effective drug release systems, with detected antibacterial activity against S. mutans.